Acceptance and Commitment Therapy (Act) on Increasing the Compliance of Management Diabetes Mellitus Type 2 - Bistara, Difran N.; Rusdianingseh,; Susanti,; Wardani, Erika M.; Septianingrum, Yurike; Ainiyah, Nur; Fitriasari, Andikawati; Noventi, Iis; Hasina, Siti N. (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes Mellitus (DM) cannot be cured but can be managed by adhering to the four pillars of DM management. A stressor occurs in patients when all their lives are required to comply with the rules for managing diabetes mellitus. Compliance with the management of the disease is one indicator of the success of patients in a treatment. Acceptance and Commitment Therapy (ACT) is a method to help individuals manage their illness and to improve the adherence of type 2 DM patients. The purpose of this study is to prove the influence of Acceptance and Commitment Therapy (ACT) in improving adherence to type 2 diabetes mellitus management. This study is a quasy experiment using method pretest posttest with control group design. Respondents in this study were patients with type 2 DM as many as 50 people and were taken by simple random sampling technique and divided into two groups, namely the intervention group and the control group. Data on compliance was obtained using a questionnaire measuring instrument. The intervention group will be given Acceptance and Commitment Therapy (ACT) for four weeks. The results of data analysis using Paired t-Test and Independent t-Test with significance p